Sea Power and the Canadian Military-Naval Industry (2010-2020) | Poder Naval e a Indústria Militar-Naval Canadense (2010-2020) - Barreto, Jéssica Pires Barbosa; Santos, Thauan (Mural Internacional, 2021)
Due to the historical difficulty of high investments in periods of conflict and large cuts in periods of peace, the Canadian military-naval industry and the country's Navy suffered from a lack of infrastructure, low technological development in some areas and scrapped equipment. After years of instability, the Harper government launched in 2010 the National Shipbuilding Strategy in an ambitious attempt to modernize the Navy and Coast Guard. Thus, the main objective of the article is to understand the role of the State as a relationship promoter within this sector and its influence on the country's naval power. The analysis is based on the Structure-Conduct-Performance (SCD) model. The research uses academic articles, documents and official reports, and is limited to 2010-2020, based on the launch of the strategy that was a milestone for the industry. Keywords: Military-Naval Industry; NSS; SCP Paradigm. RESUMO Por uma dificuldade histórica de altos investimentos em períodos de conflitos e grandes cortes em períodos de paz, a indústria naval militar canadense e a Marinha do país sofrem com falta de infraestrutura, baixo desenvolvimento tecnológico em algumas áreas e equipamentos sucateados. Após anos de instabilidades, o governo Harper lançou, em 2010, a National Shipbuilding Strategy numa ambiciosa tentativa de modernizar a Marinha e a Guarda Costeira. Dessa forma, o principal objetivo do artigo é entender o papel do Estado como promotor das relações dentro desse setor e sua influência para o poder naval do país. A análise é baseada no modelo Estrutura-Conduta-Desempenho (E-C-D). A pesquisa utiliza artigos acadêmicos, documentos e relatórios oficiais, e tem como delimitação temporal 2010-2020, baseado no lançamento da estratégia que foi um marco para a indústria. Palavras-chave: Indústria Naval-Militar; NSS; Modelo E-C-D. Recebido em: 9 nov. 2020 | Aceito em: 10 out. 2021.